Mountain Condominiums. A Discussing of Settlement and Dwelling on the Outskirts of an Alpine City - Cristina Mattiucci (Revue de Géographie Alpine)
By examining the settlement typology and the relationship between the people and the landscape where they have chosen to dwell, this paper investigates the territorial transformation processes in Roncegno Terme, a small town in the Italian province of Trento, which can be considered a paradigmatic context for metropolitan-mountain development. Starting from the model of housing that the town has been generating, we ask whether these processes manifest the features of a monofunctional residential transformation and examine the effects it may have on the transformation of the inhabited mountain and the genesis of spatial homogeneity and possible spatial inequalities.This reflection is based on a critical reading of field work carried out during an urban planning experience, and the case study is presented with the phenomenal and empirical data collected during a study about landscape perception, conceived as a structural survey to propose socially shared planning processes and territorial transformations.One of the main issues that this article tackles is the possible correlation between the shape of the newer buildings that have been erected in some areas of town and the transformation of a peri-urban mountain reality that tends to gradually take on the features of a dormitory town. The paper therefore intends to make explicit the link between the densification of the building processes and the dissolution of the collective spaces. In so doing, at the present stage of an as yet incomplete densification of the mountain settlements, we work under the assumption that this survey can be useful to reflect on the possibilities of the planning and territorial governance tools to correct the territorial disparities that might be generated when small mountain towns turn into mostly residential suburbs of the metropolitan centres nearby.